Spletno in mobilno nadlegovanje v Sloveniji - Završnik, Aleš (Revija za kriminalistiko in kriminologijo, 2012)
Cyberbullying usually refers to bullying and harassment of others by means of new electronic technologies, primarily mobile phones and the Internet. The paper presents the results of an on-line cyberbullying victimiyation survey conducted mostly among students at several Slovene faculties. 441 adults, of whom 246 were aged less than 24 years, 135 aged 24 to 35 years and 60 aged over 35 years, 304 were women and 137 men, were surveyed to examine the nature and extent of cyberbullying in Slovenia. Three main categories of cyberbullying (by email, social networking sites and mobile phones) and seven subcategories (text message bullying, email bullying, social network bullying from unknown users, social network bullying from anonymous users, posting photos in social networking sites without consent of the user, tagging faces in social networking sites without consent of the user and publishing morphed pictures without consent) were examined in relation to ageand gender, perceived impact, self-prevention measures, and turning to others in case of victimisation. There was a significant incidence of cyberbullying by email (65%), less by mobile phones (44%) and in social networking sites (22%). Gender differences were few, age difference were statistically significant (71 % of respondents aged from 24 to 35 have been bullied many times). The impact of cyberbullying was perceived as highly negative for posting personal data and photos on the Internet without consent. Frequent cybervictims would turn to police less frequently than users that have never been a victim of cyberbullying.
Keywords: abusive text messaging; analize; cyber crime; cyberbullying; internet; internet bullying; internet harrasment; interpersonal violence; kibernetska kriminaliteta; mobile phones; mobilni telefoni; preprečevanje kriminalitete; prevention of crime; sexting; Slovenia; Slovenija; social networking sites bullying; spletno nadlegovanje; zlorabe